052 Implications of new nice draft guidance for the management of recent onset cardiac chest pain at a district general hospital. (22nd September 2015) - O'Neill, J; Higham, D
Abstract : There are no nationally agreed guidelines into the investigation of troponin negative acute coronary syndromes with no ST-segment ECG changes. In February 2010 new NICE guidance is due to be published advising on the investigation and assessment of recent chest pain of suspected cardiac origin. The guidance enables the user to determine which investigation is most appropriate based on certain factors within the patient history and it may have implications for service design. We elected to study 100 consecutive patients who presented to Wansbeck General A&E over a 2-month-period with suspected cardiac chest pain which was troponin negative at 12 h. We examined which cardiac investigations were subsequently performed and then applying the proposed NICE guidance to the same patient group determined how the demand for the various investigations would alter. Overall results of this study are shown in the following Abstract 52 Table 1 : In those patients who had no known coronary artery disease (CAD) previously (61% of the population studied), 64% went on to have exercise tolerance testing (ETT), 21% had myocardial perfusion scans (MPS), 6% had invasive coronary angiography (ICA), 3% had calcium scoring ± CT angiography (CT-A) and 5% had no further investigation. Based on NICE guidance, no-one in this group of patients would have ETT. Instead, 28% would have MPS, 36% would have CT-A, 25% would have ICA and 11% would have no further investigation. These results are shown in Abstract 52 Figure 1 . In those patients with known CAD, 38% had ETT, 10% had MPS, 3% had ICA and 49% had no further investigation. Applying NICE guidance to this same group, 51% would either have ETT and MPS and 49% would have no further investigation. These results are shown in Abstract 52 Figure 2 . Conclusions: If the draft NICE Guidance is implemented, this will produce a dramatic reduction in the number of exercise tolerance tests requested. It will result in a large increase in the numbers of coronary angiograms and importantly, there will be a tenfold increase in calcium scoring and potential CT coronary angiogram requests compared with current levels. There is no significant change in demand for myocardial perfusion scans. The change in investigation profile is mostly in those patients with no pre-existing CAD. The Guidance carries significant implications for service design requiring investment into CT angiography (potentially a further 120 scans per year from just one DGH) and away from exercise testing.